PENGARUH FAKTOR-FAKTOR KESEHATAN LINGKUNGAN INDUSTRY TERHADAP TEKANAN DARAH PADA PEKERJA DI PT. X CIBITUNG, BEKASI - Asma Afifah; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
In every production process in the workplace, labor can gain exposure from environmental health factors industries such as noise, heat stress, and lighting. When the noise, heat stress, and the lighting uncompliancewithThreshold Limit Value (TLV) may cause health problems, one of them is the change in blood pressure level. This study aimed to determine the effect of environmental health factors on blood pressure in workers in PT.X Cibitung, Bekasi. The type of research was observational with cross sectional approach. The sample used in this study was the whole of population in line B and line G in PT. X Cibitung, Bekasi with non-probability sampling technique and 32 population. Analysis of data used univariate and bivariate analysis with paired T-test. The results of this study showed that there are effects of environmental health the industry on systolic (p = 0.036) and diastolic (p = 0.023)blood pressure workers. The conclusion of this study was there were the effects of environmental health industry factors on systolic and diastolic blood pressure workers. Researcher gave recommendation to companyfor having counseling programe about the effects of environmental industry to health factors (noise, lighting, and heat stress).